Betel leaf extract as an anti-bacterial agent in solid soap formulation and characterisation - Rima Wulandari; Ika Kusuma Nugraheni; Mariatul Kiptiah (Jurnal Pijar Mipa, 2023)
Used cooking oil is a waste oil derived from plants used as cooking oil. Used cooking oil can be reused by a purification process and used in soap making by a saponification process using a base (KOH or NaOH). Based on this, waste cooking oil is handled as a raw material for making solid soap. This study aimed to characterize solid soap from used cooking oil with betel leaf extract and explain the anti-bacterial ability of solid soap from used cooking oil with betel leaf extract. Solid soap is made by purifying used cooking oil by immersion in 15% NaOH and adding bleaching earth, making betel leaf extract by maceration method. The process of making solid soap with the addition of stearic acid, propylene glycol, glycerin, ethanol, and TEA. Characterization of solid soap by testing water content, amount of fatty acid, free alkaline, free fatty acid, mineral oil, foam stability, acidity test (pH), and anti-bacterial test. Testing the water content and the number of fatty acids shows that all samples did not meet the standards required by SNI 06-3532-1994. All samples in the free alkaline test (except sample F0), free fatty acids, mineral oil, and foam stability were tested to meet the standards required by SNI 06-3532-1994, and the anti-bacterial test of sample F4 has the best anti-bacterial properties because it can reduce the growth of bacteria compared to other samples.